Prevalence of early and late prematurity is similar among pediatric type 1 diabetes patients and the general population. Issue 5 (24th March 2018) - Adar, Adi; Shalitin, Shlomit; Eyal, Ori; Loewenthal, Neta; Pinhas‐Hamiel, Orit; Levy, Milana; Dally‐Gottfried, Orna; Landau, Zohar; Zung, Amnon; Levy‐Khademi, Floris; Zangen, David; Tenenbaum‐Rakover, Yardena; et al.
Abstract: Background: The incidence of type 1 diabetes mellitus (T1DM) has increased in recent decades, as has the incidence of preterm births (<37 weeks). We aimed to evaluate and compare the prevalence of prematurity and early prematurity (<34 weeks) and birth season variability among T1DM and non‐T1DM children. Methods: A nationwide cross‐sectional study was conducted, with linkage of data from 13 paediatric diabetes centers and Israeli National Registries, including T1DM patients and general non‐T1DM population, born during 2000 to 2013. Gathered data included ethnicity, gender, birth week, weight, and season. The prevalence of prematurity and birth season were compared with the general population birth registry using Pearson Chi‐square test. Results: The study population included 1452 T1DM patients, 52.7% males, and 2 138 668 subjects in the general non‐T1DM population, 51.2% males. The prevalence of late and early prematurity was similar between groups (6.1% and 2.2% in the T1DM group vs 5.6% and 2.0% in the general non‐T1DM group, P = 0.25 and P = 0.38, respectively). OR for prematurity among T1DM patients was 1.15 (0.95‐1.39), P = 0.16. No difference in birth season was demonstrated between preterm and term, in T1DM and general non‐T1DM populations. Ethiopian descent was more prevalent among T1DM patients compared with the non‐T1DM population, in both term and preterm born. Conclusions: This is the largest population‐based study, and the first in the Middle East geographical area, indicating that prematurity, including early prematurity, is not associated with T1DM during childhood. The study was registered athttps://clinicaltrials.gov/ : NCT02929953.